“A study to assess and create awareness of antirabies vaccine among care givers of tertiary care hospital” (Journal of Pharmaceutical Negative Results, 2022)
Background: Evaluative study was conducted among the care givers of tertiary care hospital Karad. The purpose of the study was to assess awareness of Antirabies vaccine among care givers of tertiary care hospital. A total no of 100 samples were selected by random sampling Results: Result of the study shows that level of knowledge among care givers in pre-test depict that (15%) were having poor knowledge and (74%) were having average knowledge and (11%) having good knowledge in pre-test. Level of knowledge in post test shows (0%) were poor knowledge and (15%) were having average knowledge and (85%) having good knowledge. Study indicated that the mean pre-test score was 10.74 and mean post test score was 17.93 the mean difference of pre-test and post test score was7.19 .The knowledge level increased so it was found statistically significant at the level of p <0.0001.This STP was effective to increase the knowledge among caregivers about Antirabies vaccines.Conclusion: Pre- test mean 10.14 and Post- test mean is 17.93. The pre-test standard deviation is 2.980136and post-test is 2.18468.The computed ‘test statistic value is 26.974, since the p value for the test is, <0.0001.Objectives: To assess Awareness of Antirabies vaccine among care givers of tertiary care hospital and to find the association between knowledge with selected socio-demographic variables. Material & methods: Evaluative study was conducted among 100 care givers in tertiary care hospital Karad. Samples were selected by purposive sampling technique. Data was collected by using pretest and posttest and was analyzed by using descriptive and inferential statistics. The current study explored about awareness on Antirabies vaccines among the caregivers and the awareness level increased among caregivers through structured teaching programme.